1990
DOI: 10.1148/radiology.175.3.2343126
|View full text |Cite
|
Sign up to set email alerts
|

Sedation in pediatric CT: national survey of current practice.

Abstract: To document current sedation practices in computed tomographic (CT) examination of children, a questionnaire was sent to a random sample of 2,000 hospitals with CT scanners in the United States. Responses were received from 834 hospitals (42%). Of these, 450 were reported to conduct pediatric CT with sedation. Approximately one-half of the examinations were conducted in pediatric hospitals or medical schools. Most hospitals did not require signed consent for CT with light sedation, even when intravenously or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Keeter et al in a review of paediatric sedation practice for CT in the USA reported that more than 80% of toddlers were sedated for CT [9]. In our study, the need for sedation declined with increasing age, from 93% in those below 1 year to under 5% for those aged 11 years and above.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Keeter et al in a review of paediatric sedation practice for CT in the USA reported that more than 80% of toddlers were sedated for CT [9]. In our study, the need for sedation declined with increasing age, from 93% in those below 1 year to under 5% for those aged 11 years and above.…”
Section: Discussionsupporting
confidence: 45%
“…Chloral hydrate is the agent mainly used in our institution, as there is general consensus that it has a wide safety margin [1], though this practice may differ from that in the USA [9]. The dose used is variable but is usually between 50 and 100 mg.kg ¹1 ; doses up to 125 mg.kg ¹1 have been ........................................................................................................................................................................................................................................... reported [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent USA survey of current practice in sedation in paediatric computer tomography, Keeter et al report that chloral hydrate is the most commonly used sedative medication [23]. Fisher considers this is fortunate: although chloral hydrate frequently results in failed sedation, it is minimally toxic [24].…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric sedation was first used widely to facilitate dental and oral surgery procedures [1][2][3] and to immobilize patients undergoing computed tomography or magnetic resonance imaging. 4,5 Subsequently, IVS has been increasingly used in the fields of pediatric oncology, 6,7 gastroenterology, 8 emergency medicine, 9,10 and several other specialties. To our knowledge, there has been no description of the use of IVS in the pediatric otolaryngology setting.…”
mentioning
confidence: 99%